2016
DOI: 10.1080/15384101.2016.1181241
|View full text |Cite
|
Sign up to set email alerts
|

Transcription elongation control by the 7SK snRNP complex: Releasing the pause

Abstract: The ability for the eukaryotic cell to transcriptionally respond to various stimuli is critical for the overall homeostasis of the cell, and in turn, the organism. The human RNA polymerase II complex (Pol II), which is responsible for the transcription of protein-encoding genes and non-coding RNAs, is paused at promoterproximal regions to ensure their rapid activation. In response to stimulation, Pol II pause release is facilitated by the action of positive transcription elongation factors such as the P-TEFb k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 103 publications
(167 reference statements)
0
39
0
Order By: Relevance
“…A variety of mechanisms have been implicated in releasing P-TEFb from 7SK complexes, including post-translational modification of 7SK snRNP components and direct interactions with RNA binding proteins or transcriptional regulators [96, 97]. The RNA splicing factor SRSF2 (also known as SC-35) was found to be part of the 7SK complex assembled at gene promoters.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of mechanisms have been implicated in releasing P-TEFb from 7SK complexes, including post-translational modification of 7SK snRNP components and direct interactions with RNA binding proteins or transcriptional regulators [96, 97]. The RNA splicing factor SRSF2 (also known as SC-35) was found to be part of the 7SK complex assembled at gene promoters.…”
Section: Discussionmentioning
confidence: 99%
“…The inactive complex occupies promoter-proximal regions on chromatin (Ji et al, 2013; McNamara et al, 2016). P-TEFb can be released from the 7SK/HEXIM complex into active complexes such as BRD4/P-TEFb (Yang et al, 2005) and the Super Elongation Complex (SEC) (Lin et al, 2010; Luo et al, 2012b; Zhou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Both cellular activators and Tat utilize CDK9 to facilitate the transcription elongation program, a critical step in the viral life cycle (Mancebo et al, 1997;Ott et al, 2011;Peterlin and Price, 2006;Zhou et al, 2000). In contrast to the cellular activators that bind cis-elements at the viral promoter, Tat binds the TAR (Transactivation Response element) RNA structure formed on nascent viral pre-mRNAs directly recruiting P-TEFb to phosphorylate Pol II and the negative elongation factors to promote 6 productive elongation (Feinberg et al, 1991;Mancebo et al, 1997;McNamara et al, 2016a;Ott et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relevance of CDK9 for activation of, both, host and viral phases of the HIV transcriptional circuit, it has long remained unclear whether both programs operate through identical or different mechanisms and how their malfunction impact proviral latency. Interestingly, recent studies have suggested a role for the transcriptional regulator KAP1 (also known as TRIM28, TIF1β) in proviral transcription through CDK9 recruitment to the promoter as part of the 7SK complex, in which the kinase remains in a primed state (D'Orso, 2016;McNamara et al, 2016a;McNamara et al, 2016b;Michels et al, 2004). In this context, the 7SK complex (composed of 7SK RNA and kinase inhibitor HEXIM) not only inactivates the kinase, but more importantly, it has a positive role in delivering the kinase for "on site" activation at the viral promoter (McNamara et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%